Efficacy of High-Dose Meropenem (Six Grams per Day) in Treatment of Experimental Murine Pneumonia Induced by Meropenem-Resistant Pseudomonas aeruginosa - Oshima, Kazuhiro (Antimicrob Agents Chemother, 2016)
High-dose meropenem (MEPM; 6 g/day) has been approved as a treatment for purulent meningitis; however, little is known regarding its in vivo efficacy in refractory lower respiratory tract infections. The purpose of this study was to evaluate the efficacy of MEPM at 6 g/day in a murine model of severe pneumonia caused by MEPM-resistant Pseudomonas aeruginosa. Experimental pneumonia induced by MEPM-resistant P. aeruginosa was treated with normal-dose MEPM (150 mg/kg of body weight, simulating a 3-g/day regimen in humans) or high-dose MEPM (500 mg/kg, simulating a 6-g/day regimen in humans). Mice treated with high-dose MEPM showed significantly restored survival relative to that of untreated mice and tended to show a survival rate higher than that of mice treated with normal-dose MEPM. The viable bacterial counts (of two clinical isolates) in the lungs decreased significantly in mice treated with high-dose MEPM from those for untreated mice (P < 0.001) or mice treated with normal-dose MEPM (P, <0.01 and <0.05). The number of inflammatory cells in the bronchoalveolar lavage fluid (BALF) was also significantly lower in mice treated with high-dose MEPM than in untreated mice. The free MEPM concentration in the epithelial lining fluid (ELF) exceeded 16 μg/ml for 85 min in mice treated with high-dose MEPM, but not for mice treated with normal-dose MEPM. Our results demonstrate that high-dose MEPM (6 g/day) might provide better protection against pneumonia caused by MEPM-resistant strains of P. aeruginosa than the dose normally administered (less than 3 g/day).